All Days 1974
DOI: 10.4043/2062-ms
|View full text |Cite
|
Sign up to set email alerts
|

Method for Predicting Geometry and Load Distribution in an Anchor Chain from a Single Point Mooring Buoy to a Buried Anchorage

Abstract: Procedures· are developed for estimating geometry and load distribution in a chain connected from a floating object t·o a fixed anchor beneath the seabed. Previously published information on this subj ect has been restricted to a discussion of resistance of soil to movement of chain normal to the chain path. This paper expands the theory to include procedures for considering tangential resistance of soil to movement of the chain, the effective weight of chain in soil, and the general case of chain entering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The foundation load at the padeye becomes smaller than the corresponding line load at the mudline, and the loading angle at the padeye will be greater than the loading angle at the mudline. Gault and Cox (1974) observed that the soil resistance normal to the chain has little influence on the total load transferred to the padeye but has a greater influence on the direction of a line. The soil resistance results in an inverse-catenary mooring line shape of the embedded chain.…”
Section: "Seplamentioning
confidence: 97%
“…The foundation load at the padeye becomes smaller than the corresponding line load at the mudline, and the loading angle at the padeye will be greater than the loading angle at the mudline. Gault and Cox (1974) observed that the soil resistance normal to the chain has little influence on the total load transferred to the padeye but has a greater influence on the direction of a line. The soil resistance results in an inverse-catenary mooring line shape of the embedded chain.…”
Section: "Seplamentioning
confidence: 97%
“…Behaviour of the embedded chain may be obtained by integrating the governing equilibrium from one end of the chain to the other [13,[16][17][18][19]. Here T is the tension in the chain acting over the incremental chain length ds, θ the chain angle to the horizontal, wc the submerged weight of chain per unit length, and Q and F respectively the normal and frictional soil resistances per unit length in the directions perpendicular and parallel to the chain axis.…”
Section: Appendix -Existing Design Relationshipsmentioning
confidence: 99%
“…Previously, the only available method for predicting the resulting anchor chain profile and load development involved numerical integration of the governing differential equations, together with iteration of one of the unknown boundary conditions in order to match the known boundary conditions, This method was initially performed using small circular elements of chain, as presented by Reese (1973) and Gault & Cox (1974). Vivatrat et al (1982) simplified the method by assuming small curvi-linear chain segments.…”
Section: Introductionmentioning
confidence: 99%